Tinjauan Ketepatan Pengodean Diagnosis Penyebab Dasar Kematian pada Pasien Diabetes Mellitus di RSU UKI Jakarta - Nurmalasari, Dinda; Widjaja, Lily; Rosmala Dewi, Deasy; Indawati, Laela (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Determination is a precaution and the accuracy of disease codes can be easily identified into correct and incorrect codes, Correct codes are adjusted in ICD-10 then incorrect codes are inappropriate codes in ICD-0. The cause of death was hospital reporting. The uncertainty of the diagnostic code consists of 5m (man, money, method, machine, material) based on the interview of the coding officer that the precision of the cause of death in the diabetes mellitus diabetes is not optimum because of poor doctors' writing, the use of abbreviations in the diagnosis, the lack of human resources in rmic education, no charge in coding, The method of conducting a death certificate from the medical certificate form is the cause of death at the point of immediate cause, the cause between and the underlying cause and the absence of a specialized chamber. Hence, the authors conducted a study on the correctness of the causes of death in diabetes patients mellitus according to the icd-10. The purpose of this study was to understand the precision of the diagnosis of the causes of death in the diabetes patient mellitus in Jakarta general hospital. Based on a study of the 72 medical records of patients dying of the precision of the cause of death in diabetes patients mellitus in Jakarta general in 2017-2020.